Oscar Wilde's short stories - Heward, Victoria; Manna, Giovanni, 1966-; Wilde, Oscar, 1854-1900. (Genoa [Italy] : Black Cat Pub., 2003)
A collection of short fairy tales originally written by Oscar Wilde for his two young sons, with an audio CD featuring full recordings of the text.
Accompanying CD includes a recording of the text with additional listening activities.
Young Adult
Keywords: Readers; Reading materials